Relationship of Family Support with Vegetable and Fruit Consumption Behavior (Indian Journal of Forensic Medicine & Toxicology, 2020)
The family approach is the development of a home visit by the public health center effort. one of theactivities is community management support system in supporting a culture of healthy living in the family.Family support is needed to behave in the consumption of vegetables and fruit every day. Clean and healthyliving behavior in the household or family structure is one of the goals in clean and healthy behavior.There are 10 indicators of clean and healthy behavior in family settings, one of them is the consumption ofvegetables and fruit every day. This study aims to analyze the relationship between family support and theconsumption of vegetables and fruits in children. The research design used in this study is research crosssectional. The research sample is Golden Christian School elementary school students. The time of the studywas in May and June 2018. The results showed that there was no significant relationship between emotionaland assessment support for vegetable and fruit consumption behavior in children. There is a significantrelationship between instrumental support and information support with vegetable and fruit consumptionbehaviors in children, respectively p-value 0.015 and 0.041. It is recommended that the school provideknowledge to parents whose children are vulnerable not to consume vegetables and fruits in order to supportthe healthy indonesia program with a family approach.
Keywords: family support, behavior, consumption, vegetables, fruit